Negative Sentiments Study of Buton Kraton Fortress: How Environmental Factors Play Role in Maintaining the Historical and Cultural Site - Syahadat, Ray March; Baiquni, Muhammad; Fandeli, Chafid; Widiyastuti, Dyah (Universitas Diponegoro Publishing Group, Indonesia, 2024)
Baubau City has the Buton Kraton Fortress, which is the largest fort in the world and an iconic tourist attraction in the city. Studies regarding tourists' bad experiences related to tourism at the Buton Kraton Fortress have not yet been explored. Bad experiences in cultural tourism activities can give rise to negative sentiments that influence visits to a destination. We used three approaches to explore this negative sentiment, namely interviews with five tourists who had come to enjoy the fort as well as a key person, autoethnography, and netnography. This study aims to explore negative sentiment in the Buton Kraton Fortress. The results show that negative sentiment by tourists, the local community, and online communities most often highlight the problems of waste, spatial and green planning, and city infrastructure. Talking about Buton Kraton Fortress cannot be limited to just the area surrounded by the fort structure but also the surrounding environment. It is very important to note that in planning and managing Buton Kraton Fortress, the approach used must be in line with history and culture itself. The aspects of authenticity, originality, uniqueness, variety, beauty, and integrity are the basis that must always be used because negative sentiment arises when these six aspects are not considered in the planning and management of the Buton Palace Fortress and its surrounding environment.